INTELIGÊNCIA EMOCIONAL, CAPITAL PSICOLÓGICO E PERCEPÇÃO DE SUPORTE ORGANIZACIONAL EM GESTORES DO SEGMENTO DE SAÚDE - Esboriol, Valéria (2013)
The healthcare industry is heavily impacted by several factors and is considered one of the most important branches of the Brazilian economy. The healthcare professional is challenged to meet the management of issues for which it was not developed in his academic educational process. Whereas emotionally intelligent people and at the same time carrying positive psychological states that integrate psychological capital,have a psychic structure that enables them to achieve leadership positions,this study aimed to interpret and discuss the correlations between emotional intelligence,psychological capital and perception organizational support. Study participants were 123 managers with academic health degree and experience in the health industrie. Data collection was conducted through self-administered electronic questionnaire and data were analyzed using descriptive and bivariate analysis through SPSS software in its version 19.0 . It was evident that these professionals possess in greater evidence of self awareness the ability of emotional intelligence, on the other hand have limitations on the availability and the establishment of personal relationships (sociability) as relevant in the management process.Already dimensions related to psychological capital , focused on job performance , demonstrated that this professional is confident in its ability to contribute to company goals and to overcome possible obstacles inherent in their work activities. Added to your psychological capital to support the perception that the organization can offer you support when you need to feel good and perform their tasks.